Aplikasi Antibakteri Nanopartikel Perak (NPAg) Hasil Biosintesis dengan Ekstrak Air Daun Kemangi: Application of Antibacterial from Silver Nanoparticles (AgNPs) Biosynthesis with Basil Leaf Extract - Gusti Ayu Dewi Lestari; Pande Made Desy Ratnasari; James Sibarani (Chemistry Department, Mathematics and Natural Science Faculty, Tadulako University, 2022)
Nanotechnology is a technology that can be used to overcome several environmental problems. Synthesis of silver nanoparticles (AgNPs) mediated with basil leaf bioreductant with a concentration 0.5% at a temperature of 25⁰C has been carried out. The result of biosynthesis of AgNPs was analyzed using a UV-Vis spectrophotometer in which the SPR band showed the maximum wavelength of 429 nm. The size of AgNPs was determined by a Particle Size Analyzer (PSA), which its size was 86.83 nm. The morphology and elemental content of AgNPs were confirmed using SEM-EDS showing that the shape of AgNPs was irregularly spherical crystals while the EDS results showed a dominant peak at 3 keV indicating silver content. AgNPs showed strong antibacterial activity against Escherechia coli and moderate against Staphylococcus aureus.